Sustainable Strategies and Factors Influencing IoT Adoption Frameworks in Library Management in Educational Institutions: A Systematic Literature Review [version 2; peer review: 2 approved] - Sulaiman Saleem PATEL; Oluwasegun Julius Aroba; Frank Boateng (Routledge Open Research, 2025)
The study offers a systematic literature review on the factors influencing IoT adoption in library management while maintaining a sustainable strategy focused on educational institutions to gain insights and identify challenges and trends. The challenges include security and privacy, infrastructure costs, standards, regulatory compliance, and institutional readiness. The methodology employed in the review adhered to the PRISMA framework, ensuring a comprehensive and transparent process anchored in the factors influencing IoT adoption in university library management. It covers studies from 2020 to 2024 and 30 IoT adoption-related articles published. In addition to the PRISMA guidelines, the TCCM framework was used in the study, which identifies empirical themes within Technology Acceptance Models (TAM, UTAUT, DOI) to uncover the root causes driving perceptions of perceived usefulness and perceived ease of use. Consequently, the study conducted a systematic literature review (SLR) by retrieving 496,858 articles from Web of Science, Scopus, and Emerald between 2020 and 2024, with 30 articles selected for in-depth quality assessment following a rigorous viability process. Furthermore, the study proposed sustainable improvement solutions for user experience arising from the factors influencing the adoption of IoT in library management systems.